Knowledge and Practice Survey on Zika Virus Infection Among General Adults in Brunei Darussalam. (May 2019) - Chaw, Li Ling; Tuah, Nik Anni Afiqah; Idris, Fazean Irdayati; Wong Yun Yaw, Justin; Naing, Lin
A cross-sectional survey was conducted to assess the knowledge and practices on Zika virus infection among general adults in Brunei Darussalam. From February to June 2017, 439 adults were interviewed from outpatient health care settings. Most participants were Malays (87.0%) and females (61.5%), with a mean age of 40.7 years. Only 25.1% had a total knowledge score of 15 to 28 points (of a possible score of 0-28). Females and those living in households of <8 people were more likely to have higher total knowledge scores (15-28 points). Media was the preferred source to get updates. Also, 67.4% had a total prevention practice score of 19 to 36 points (of a possible score of 0-36). Those who attained secondary level education or below, had no pregnant women present in their household, and scored 15 to 28 points for knowledge were more likely to have higher prevention practice scores (19-36 points). Knowledge on Zika was significantly associated with prevention practices against mosquito bites and breeding.